Correction to: Date fruit melanin is primarily based on (−)-epicatechin proanthocyanidin oligomers (Scientific Reports, (2024), 14, 1, (4863), 10.1038/s41598-024-55467-x) - Alam, Muneeba Zubair; Okonkwo, Clinton Emeka; Cachaneski-Lopes, João P. [UNESP]; Graeff, Carlos F. O. [UNESP]; Batagin-Neto, Augusto [UNESP]; Tariq, Saeed; Varghese, Sabu; O’Connor, Matthew J.; Albadri, Abuzar E.; Webber, J. Beau W.; Tarique, Mohammed; Ayyash, Mutamed; et al. (Springer Nature, 2024)
Correction to: ScientificReportshttps://doi.org/10.1038/s41598-024-55467-x, published online 28 February 2024 The original version of this Article contained an error in the spelling of the author João P. Cachaneski-Lopes which was incorrectly given as João P. Cachaneski-Lope. The original Article has been corrected.